Maid in Manhattan [videorecording (DVD)] - Wang, Wayne, 1949-; Lopez, Jennifer, 1970-; Fiennes, Ralph; Richardson, Natasha (Columbia TriStar Home Entertainment, 2003)
A struggling single mom takes a job as a chambermaid at a luxury hotel in New York. She meets and falls in love with a suave and sophisticated heir to an American political dynasty, who mistakes her for a society woman. When her real identity is revealed, the reality about their separate lives sets in.